Deciphering the Pharmacological Mechanisms of the Huayu-Qiangshen-Tongbi Formula Through Integrating Network Pharmacology and In Vitro Pharmacological Investigation - Wang, Zihao; Linghu, Ke-Gang; Hu, Yuanjia; Zuo, Huali; Yi, Hao; Xiong, Shi-Hang; Lu, Jinjian; Chan, Ging; Yu, Hua; Huang, Run-Yue (Frontiers in Pharmacology, 2019)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, causing articular and extra articular dysfunctions among patients, and it could lead to irreversible joint damage or disability if left untreated. Traditional Chinese medicine (TCM) formula, Huayu-Qiangshen-Tongbi (HT) formula, has been found successful in controlling RA in TCM clinics. In this study, we conducted a systematic analysis of the HT formula with a purpose of proposing the potential mechanism of action (MOA) for it by using network pharmacological methods. The potential targets of the formula were collected and screened according to the topological features of their protein-protein interaction (PPI) network, and we subsequently validated our prediction results through in vitro experiments. We proposed that HT formula could interfere with the bone metabolism and the inflammatory pathways of the body. The experimental validation results indicated that HT formula could exhibit anti-inflammatory effects by regulating several signaling pathways including the Toll-like receptor signaling pathway, PI3K - Akt signaling pathway, HIF-1 signaling pathway, MAPK signaling pathway and AP-1 signaling pathway.